Biochemical characterization of the GTP-sensing protein, CodY of Bacillus anthracis. Issue 4 (3rd May 2017) - Joon, Shikha; Gopalani, Monisha; Rahi, Amit; Kulshreshtha, Parul; Gogoi, Himanshu; Bhatnagar, Sonika; Bhatnagar, Rakesh
Abstract: The pleiotropism of the GTP-sensing transcriptional regulator CodY is evident by the gamut of processes that it regulates in almost all low G+C Gram-positive bacteria, including general metabolism, biosynthesis of some amino acids and transport systems, nitrogen uptake, sporulation, biofilm formation, motility and virulence. The role of CodY in virulence has been established in Bacillus anthracis, the top rated bioterrorism agent. In this study, we investigated the biochemical attributes of this global regulator. Homology modeling and sequence/structure analysis revealed putative GTP-binding residues in CodY of B. anthracis . CodY exhibited an interaction with the GTP as tested by ultraviolet cross-linking experiments. It could autophosphorylate itself at a conserved Ser 215 residue. This was further corroborated by the impairment of autophosphorylation activity in the CodYS215A mutant. Autophosphorylation may be speculated as an additional mechanism regulating CodY activity in the cell. The protein could also hydrolyze GTP, albeit weakly, as indicated by thin- layer chromatography and spectrophotometric quantification of its kinetic parameters. Altogether, these observations provide us an insight into the mechanism of action of this global regulator and a better understanding of its functional regulation. Abstract : CodY of Bacillus anthracis binds to and hydrolyze GTP and autophosphorylates itself at a conserved serine residue.